Engineer Teachers' perspectives on tutoring at university - Jimena Vanina Clérici Tealdi; Rita Lilian Amieva Camargo (Universitat Politècnica de València, 2013)
In Argentina, the educational changes at university level that have taken place for the last decades have aimed at influencing both the syllabus and teachers' culture. In the former case, the changes have been achieved by organizing education on the basis of competences; in the latter case, this has been done by integrating teacher tutoring to education. In the context of these significant changes, and in work contexts that do not foster the discussion of these changes, it is important to examine how these changes are integrated, what meanings teachers assign to them, and what implications the changes have for the teachers. In order to address these questions, we present preliminary results of a doctoral thesis that approaches the study of university teachers' perspectives about the changes proposed for engineering careers. Specifically, we present the perspectives about tutoring that a group of teacher tutors has in the context of the School of Engineering at Universidad Nacional de Río Cuarto (UNRC), Argentina. The analysis of documents and interviews as well as our observations allowed us to identify at least two perspectives: on that considers tutoring as a peripheral activity, and another that considers tutoring as an activity integrated to undergraduate teaching. These perspectives are related to other perspectives about educational changes in a wider context, those which make it possible to understand how the changes are produced and what aspects facilitate or impede them.